Dream Big: Reviving a Kansas Grain Mill - Cindy Hoedel (Symphony in the Flint Hills, 2016)
The back side of the abandoned limestone mill soars four stories into a tree canopy from the tea-colored Cottonwood River that laps at its base.
Keywords: limestone; cracks; Dan Clothier; red-and-black turbo; JAWOOHL; Wyoming Mills; cattleman; symphony; artwork; landscapes; MILL WORKS; Dave Leiker; MILL AND LOG JAM; PRAIRIE; REMEMBERED 2; Kelly Yarbrough